Tobacco treatment clinics in urban public housing: feasibility and outcomes of a hands-on tobacco dependence service in the community - Panagis Galiatsatos; Alexandria Soybel; Mandeep Jassal; Sergio Axel Perez Cruz; Caroline Spartin; Katie Shaw; Jodi Cunningham; Norma Fox Kanarek (BMC, 2021)
Abstract Background As a further extension of smoke-free laws in indoor public places and workplaces, the Department of Housing and Urban Development's declaration to propose a regulation that would make housing units smoke-free was inevitable. Of note is the challenge this regulation poses to current tenants of housing units who are active smokers. We aimed to assess the efficacy of a tobacco treatment clinic in public housing. The utilization of the clinic by tenants and tenants' respective outcomes regarding smoking status were used to determine the intervention's effectiveness. Methods Tobacco treatment clinics were held in two urban-based housing units for 1-year. The clinics provided on-site motivational interviewing and prescriptions for pharmacological agents if warranted. Outcomes collected include the tenants' clinic attendance and 3- and 6-month self-reported smoking status. Results Twenty-nine tobacco treatment clinic sessions were implemented, recruiting 47 tenants to participate in smoking cessation. The mean age of the cohort was 53 ± 12.3 years old. Of the 47 tenants who participated, 21 (44.7%) attended three or more clinic sessions. At the 3-month mark, five (10.6%) tenants were identified to have quit smoking; at 6-months, 13 (27.7%) tenants had quit smoking. All 13 of the tenants who quit smoking at the end of 6-months attended three or more sessions. Conclusion An on-site tobacco treatment clinic to provide strategies on smoking cessation was feasible. Efforts are warranted to ensure more frequent follow-ups for tenants aiming to quit smoking. While further resources should be allocated to help tenants comply with smoke-free housing units' regulations, we believe an on-site tobacco treatment clinic is impactful.